PEMBERDAYAAN MASYARAKAT PESISIR BERBASIS KELUARGA PERSEPEKTIF GENDER - Sutarto, Dendi (JURNAL TRIAS POLITIKA, 2018)
Abstract Empowerment analysis of coastal communities in Batam, Karimun, and Lingga Islands based on family aims to find out strategies, models and what factors influence the empowerment of coastal communities. This analysis is useful to provide a solution and model recommendations to improve the independence and empowerment of the community in a sequential manner. This study is a qualitative descriptive method analysis with a gender approach. Factors affecting sustainable community empowerment; Learning by doing, problem solving, self evaluation, self development and coordination, self selection, self decisive independent variables. This concept provides direction in achieving the objectives of empowering the coast community of Batam, Lingga and Karimun as island coastal communities, with all the enormous natural potential, therefore all they need human resources as a power to manage the potential of the sea, fisheries, agriculture, home industry there is. There is great confidence in the power of human resources as a word view or the way they see the world, the potential that has social, economic value and so on as a great power for them. Keywords: Empowerment, Coastal Community, Family, Gender  AbstrakKajian Pemberdayaan Masyarakat pesisir Batam, Karimun, dan Kepulauan Lingga berbasis keluarga bertujuan untuk mengetahui startegi, model dan faktor-faktor apakah yang mempengaruhi dalam pemberdayaan masyarakat pesisir. Analisis ini bermanfaat untuk memberikan rekomedasi solusi dan model untuk meningkatkan kemandirian dan pemberdayaan masyarakat secara berkenjutan. Kajian ini merupakan analsis metode deskriptif kualitatif dengan pendekatan gender. Faktor-faktor yang mempengaruhi pemberdayaan masyarakat secara berkelanjutan; Learning by doing, Problem solving, Self evaluation, Self development and coordination, Self selection, Self decisim independent variable. Konsep ini memberikan arah dalam pencapaian tujuan pemberdayaan masyarakat pesisi Batam, Lingga dan Karimun sebagai masyarakat pesisir kepulauan, dengan segenap potensi alam yang sangat besar, dengan itu semuan mereka membutuhkan sumber daya manusia sebagai kekuatan untuk mengelola potensi laut, perikanan, pertanian, home industry yang ada. Ada keyakinan besar dengan kekuatan sumber daya manusia sebagai word view atau cara mereka melihat dunia, potensi yang memiliki nilai sosial, ekonomis dan sebagainya sebagai kekuatan besar bagi mereka. Kata kunci: Pemberdayaan, Masyarakat Pesisir, Keluarga, Gender